Implementation of Digital Payment in Mitigation of Fraud Risk at Hotel Conrad Bali - Fadya, Ni Made Tiana; Widawati, Ida Ayu Putri; Rukmiyati, Ni Made Sri (Indonesian Journal of Banking and Financial Technology, 2024)
This study aims to be a fraud risk mitigation strategy in managing payment transactions. This study is a qualitative study. Data collection by interviews, documentation studies, and observations. Data analysis techniques used in this study are data reduction, data presentation, and drawing conclusions. The results of this study indicate that digital payments in payment transactions at Conrad Bali use internet banking. Conrad Bali conducts a longitudinal risk evaluation to identify fraud and applies a clear separation of duties. Conduct routine audits of security systems and internal controls to ensure employee effectiveness. Authorization is carried out with three security procedures, namely transaction maker (account payable and paymaster), approver/checker (chief accountant, OIBH, director of finance, and general manager) and releaser (general manager and owner).